2020
DOI: 10.1017/s1930297500008238
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Butler and Pogrebna (2018) using true and error model

Abstract: Butler and Pogrebna (2018) devised triples of three-branch gambles theorized to violate transitivity of preference according to a most probable winner model. According to this model, a person chooses the option that has the higher probability to yield a better outcome than the other alternative. They tested 11 triples with 100 participants and found cases that appeared to violate weak stochastic transitivity and the triangle inequality. But tests of weak stochastic transitivity and the triangle inequality do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Four of the 11 triples had estimated incidences of intransitive behavior that were statistically significant, according to the TE analysis. Birnbaum (2020) and Butler (2020) agreed that the stimuli of Butler and Pogrebna (2018) had generated systematic evidence of violation of transitivity and that this design should be pursued in further investigations of this property.…”
Section: Criticisms Of Transitivity Researchmentioning
confidence: 59%
See 1 more Smart Citation
“…Four of the 11 triples had estimated incidences of intransitive behavior that were statistically significant, according to the TE analysis. Birnbaum (2020) and Butler (2020) agreed that the stimuli of Butler and Pogrebna (2018) had generated systematic evidence of violation of transitivity and that this design should be pursued in further investigations of this property.…”
Section: Criticisms Of Transitivity Researchmentioning
confidence: 59%
“…A reanalysis of the Butler and Pogrebna data using a true and error (TE) model found that there was modest, but statistically significant evidence of systematic violations of transitivity (Birnbaum, 2020): It was estimated that 11% of the preference patterns were compatible with MPW, and about 18% were intransitive preferences of the opposite type. Four of the 11 triples had estimated incidences of intransitive behavior that were statistically significant, according to the TE analysis.…”
Section: Criticisms Of Transitivity Researchmentioning
confidence: 99%
“…Müller-Trede (personal communication, Jan. 3, 2020) reanalyzed the data of Müller-Trede, et al (2015, Experiment 1) and found that 5 of 22 participants had estimates of probability of the predicted intransitive pattern significantly exceeding 0; for these same 5, the authors had rejected the triangle inequality. Birnbaum (2020) reanalyzed data from Butler and Pogrebna (2018) and found that 3 of the 11 triples they tested showed significant probabilities of the intransitive preference pattern predicted by the most probable winner model, with rates of this violation ranging from 34% to 51% in the three cases that were significant.…”
Section: Appendix C: Incidence Of Intransitive Preferencesmentioning
confidence: 99%
“…
Birnbaum (2020) reanalyses the data from Butler and Pogrebna (2018) using his 'true and error' test of choice patterns. His results generally support the evidence we presented in that paper.
…”
mentioning
confidence: 99%
“…It would be useful to understand how to apply or extend the true and error model for the comparisons between an individual's binary and ternary choices, as that is a key part of our study of intransitivity in the paper. There are two other observations we would like to make regarding Birnbaum (2020). The first concerns his remarks on the evidence for most probable winner (MPW) cycles, and the second, on the significance of predictably intransitive choice patterns.…”
mentioning
confidence: 99%